The Analysis of Guided Inquiry Learning Model Influence towards Primary School Students Science Learning Outcomes - I Putu Agus Adi Saputra; I Made Citra Wibawa; I Made Suarjana (Universitas Pendidikan Ganesha, 2020)
The research that examines the effect of guided inquiry learning models on science learning outcomes has been done a lot, but the results of these studies have not received further study to be summarized and re-tested the effectiveness of the effects of the learning model used. This study aimed to determine the effect of guided inquiry learning models on the science learning outcomes of elementary students. This research was library research with meta-analysis data analysis techniques. The subjects of this study were 7 research articles from various Sinta accredited research journals. Data collection used literature study techniques which were followed by reviewing articles related to the research topic. This study analyzed the effect size of each article. The results of the analysis of the value of each research article obtained the highest value of 1.34, which is included in the large category and there is a research article obtaining a value of 0.78 which has a medium category. Based on the results of the analysis, it was concluded that the guided inquiry learning model has a great influence on improving the learning outcomes of elementary school science students. It also reinforces the results of previous research which states the guided inquiry learning model has a positive effect on improving science learning outcomes of elementary school students.